Sustainability assessment of Cerrado and Caatinga biomes in Brazil: A proposal for collaborative index construction in the context of the 2030 Agenda and the Water-Energy-Food Nexus - Gustavo Felipe Balué Arcoverde; Julia Alves Menezes; Mariana Gutierres Arteiro Paz; Jocilene Dantas Barros; Janaína Ferreira Guidolini; Evandro Albiach Branco; Pedro Ribeiro De Andrade; Sergio Mantovani Paiva Pulice; Jean Pierre Henry Balbaud Ometto (Frontiers in Physics, 2023)
The 2030 Agenda framework represents an opportunity for the co-development of local indicators and shares the same principles of cross-sectoral integration and universality as the water–energy–food nexus. This research aimed to develop a quantitative-collaborative methodology for constructing indicators and indexes for the sustainability of the Cerrado and Caatinga Brazilian biomes, considering the connection and synergies between the Nexus perspective and the 2030 Agenda’s SDG–target framework. The study was applied in 2,512 municipalities that make up the total of the mentioned biomes. The methodology consists of four major blocks: i) identification and construction of indicators based on the association of them with one or more 2030 Agenda’s targets, in a collaborative way from expert groups; ii) generation of weights by an indicator considering leverage, according to the number of target assignments, and importance, attributed by experts for each indicator to the target; iii) generation of sustainable development goal indexes, considering the performance of the SDGs; Nexus performance, considering different weights between the SDGs; Nexus synergistic, the standard deviation between the SDGs; and Nexus overall, a combination of the last two; and iv) sensitivity analysis for performance indexes considering the assignment of zero values to the governance indicators. In general, the regions of MATOPIBA, northern and western of Cerrado and the Caatinga, are, on average, the areas of greatest vulnerability. The targets that respond to this inequality are related to eradicating hunger, sustainable and climate-resilient production systems, universal access to water, water quality, efficiency of multiple water uses, access to energy, and the participation of renewable energies. We found that in areas of better average nexus performance, there is also greater inequality between nexus dimensions; therefore, the Nexus overall index is penalized. The federal units and areas with the worst Nexus dimension performances and with insufficient governance measures are north and northwest of Bahia and municipalities bordering the State of Tocantins—food; Maranhão and Piauí, northeast of Mato Grosso, northwest of Goiás, Rio Grande do Norte and Paraíba—water; and Maranhão, extreme southeast of Pará, and more sparsely in Paraíba—energy.